Epidemiología descriptiva y genética molecular del cáncer de mama hereditario en Costa Rica - García-Jiménez, Laura (2012)
Descriptive epidemiology and molecular genetics of hereditary breast cancer in Costa Rica. Breast cancer is first in incidence and mortality among Costa Rican women. In 2011 there is a projected 1 071 new cases. We selected 116 patients diagnosed with breast cancer and family history of breast cancer. A detailed family history and epidemiology data was obtained from each patient and a blood sample was processed for DNA extraction. We analyzed the prevalence of risk factors and BRCA1 and BRCA2 mutations. These muta- tions were detected by different techniques and were confirmed by direct sequencing. Six patients (5.2%) had a mutation, five of which were in the BRCA2 gene and only one in BRCA1. We found that the average age of women who carry a mutation is lower than in non-carrier women. All other risk factors analyzed were not dif- ferent among carrier and non-carrier women. In addition, these results and the increased incidence of breast cancer in recent years in Costa Rica, should promote an increase in prevention policies and the establishment of efficient detection methods that allow early disease diagnosis.